EXPERIMENTAL STUDY ON SELFCOMPACTING CONCRETE CONTAINING INDUSTRIAL BY-PRODUCTS - Pai, B.H.V.; Nandy, M.; Krishnamoorthy, A.; Sarkar, P.K.; Pramukh Ganapathy, C. (European Scientific Journal, ESJ, 2014)
Self-Compacting Concrete (SCC) is a type of concrete that has thecapacity to consolidate under its own weight. The current trend all over theworld is to utilize the treated and untreated industrial by-products, domesticwaste etc. as a raw material in concrete, which gives an eco-friendly edge tothe concrete preparation process. This practice not only helps in reuse of thewaste material but also creates a cleaner and greener environment. This studyaims to focus on the possibility of using industrial by-products like GroundGranulated Blast furnace Slag (GGBS) and Silica fumes (SF) in preparationof SCC. The usage of these powders is proposed as a replacement for cementin the production of SCC by adopting the much popular Nan Su et al. methodof mix design. The paper deals with comparison of performances of GGBSand SF based SCC mixes.